Flexible cerebral connectivity patterns subserve contextual modulations of pain. - Ploner, M; Lee, M; Wiech, K; Bingel, U; Tracey, I (2011)
The perception of pain can be significantly modulated by the behavioral context. Here, we investigated how contextual modulations of pain are subserved in the human brain. We independently modulated the attentional and emotional context of painful stimuli and recorded brain activity by using functional magnetic resonance imaging. Our results confirm that attention to pain and a negative emotional context increases pain perception and this is concomitantly associated with increased neural activity in the anterior insular cortex. Connectivity analyses further reveal that during attentional and emotional modulations of pain, the anterior insula selectively and flexibly connects to attentional and emotional brain networks in frontoparietal and medial temporal lobe areas, respectively. We conclude that the flexible functional connectivity of the anterior insula to other functional systems of the brain, for example, attentional and emotional brain networks, subserves the extraordinary sensitivity of the pain experience to contextual modulations.